2010
DOI: 10.1101/gr.102210.109
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary constraint facilitates interpretation of genetic variation in resequenced human genomes

Abstract: Here, we demonstrate how comparative sequence analysis facilitates genome-wide base-pair-level interpretation of individual genetic variation and address two questions of importance for human personal genomics: first, whether an individual's functional variation comes mostly from noncoding or coding polymorphisms; and, second, whether populationspecific or globally-present polymorphisms contribute more to functional variation in any given individual. Neither has been definitively answered by analyses of existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 65 publications
6
90
0
Order By: Relevance
“…If we also consider the deep intronic polymorphic variants that have the potential to confer susceptibility to disease Emison et al, 2005;Fraser and Xie, 2009;Grant et al, 1996;Mann et al, 2001;Susa et al, 2008], it is very likely that splicing-relevant intronic variation will have been seriously underascertained thus far. Consistent with this statement, Goode et al [2010] have recently reported that the vast majority of putatively functional variants in the human genome actually reside in either intronic or intergenic locations. …”
Section: Intronic Mutationssupporting
confidence: 53%
See 1 more Smart Citation
“…If we also consider the deep intronic polymorphic variants that have the potential to confer susceptibility to disease Emison et al, 2005;Fraser and Xie, 2009;Grant et al, 1996;Mann et al, 2001;Susa et al, 2008], it is very likely that splicing-relevant intronic variation will have been seriously underascertained thus far. Consistent with this statement, Goode et al [2010] have recently reported that the vast majority of putatively functional variants in the human genome actually reside in either intronic or intergenic locations. …”
Section: Intronic Mutationssupporting
confidence: 53%
“…Finally, it should be understood that whereas the deleteriousness of the average synonymous mutation is always likely to be less than that of that of a nonsynonymous (missense) mutation , the higher prevalence of synonymous mutations means that they may actually make a significantly greater contribution to the phenotype than nonsynonymous mutations [Goode et al, 2010].…”
Section: Coding Sequence Mutationsmentioning
confidence: 99%
“…Functionally important regions of the genome show much lower degrees of genetic variation than others with no known function (e.g., coding versus noncoding; Fig. 1A; Goode et al 2010;Mu et al 2011). Exonic variants that have become common in the population (frequency $5%) are overabundantly synonymous (do not change the amino acid encoded).…”
Section: Neutral Theory For Personal Population and Species Differementioning
confidence: 99%
“…Specifically, GERP scores represent the deficiency in the number of substitutions at putatively functional sites compared to the number of substitutions seen in neutral DNA. Thus, the lower the number of substitutions at a site across the phylogeny, the higher the level of purifying selection at that site (Goode et al 2010;Henn et al 2016). We used the same approach as Henn et al (2015) for the GERP score annotation.…”
Section: Annotation Of Variantsmentioning
confidence: 99%